Efficacy of EMCO Therapy on Serum β-hCG Levels in Case of Gestational Trophoblastic Neoplasm (GTN) at Dr. M. Djamil Hospital Padang 2019-2021 - Siregar, Attahhal Fikrian Syadiq; Syamel Muhammad; Elly Usman (Andalas Obstetrics And Gynecology Journal, 2024)
Backgrounds: Etoposide, Methotrexate, Cyclophosphamide, and Vincristine (EMCO) Chemotherapy is used as an alternative therapy for patients with a diagnosis of Gestational Trophoblastic Neoplasm (GTN) at Dr. M. Djamil Hospital Padang because Actinomycin D has not been included in the National Formulation (FORNAS). Purpose: To determine the efficacy of EMCO therapy with limited Actinomycin D on serum Î²-hCG levels in Gestational Trophoblastic Neoplasm (GTN) cases at Dr. M. Djamil Padang Hospital in 2019-2021. Methods: The type of research used is numerical comparative analytics with a cross sectional approach. The number of samples was 17 GTN patients who had done EMCO chemotherapy and checked Î²-hCG levels before and after chemotherapy. The research was conducted from April to October 2022 at Dr. M. Djamil Hospital Padang. Data processing using total sampling technique and tested using Wilcoxon Test. Results: Most GTN patients were found to be <40 years old (64,7%), history of molar hydatidiform pregnancy (47,1%), last pregnancy interval <4 months (58,8%), Î²-hCG level before chemotherapy ranged from 104-105 mIU/mL (52,9%), tumor size >5 cm (58,8%), metastasis location in the internal genital tract (35,5%), and patients who did not have metastasis (52,9%). Conclusion: There was a significant decrease in Î²-hCG levels after chemotherapy using EMCO for three cycles in patients with a diagnosis of GTN.